Corrosion Monitoring of Flexible Metallic Substrates for Dye-Sensitized Solar Cells - Trystan Watson; Gavin Reynolds; David Wragg; Geraint Williams; David Worsley (International Journal of Photoenergy)
Two techniques for monitoring corrosion within a dye-sensitized solar cell (DSC) system are presented, which enable continuous, high sensitivity, in situ measurement of electrolyte breakdown associated with DSCs fabricated on metals. The first method uses UV/Vis reflectance spectrophotometry in conjunction with encapsulation cells, which incorporate a 25 μm thick electrolyte layer, to provide highly resolved triiodide absorption data. The second method uses digital image capture to extract colour intensity data. Whilst the two methods provide very similar kinetic data on corrosion, the photographic method has the advantage that it can be used to image multiple samples in large arrays for rapid screening and is also relatively low cost. This work shows that the triiodide electrolyte attacks most metals that might be used for structural applications. Even a corrosion resistant metal, such as aluminium, can be induced to corrode through surface abrasion. This result should be set in the context with the finding reported here that certain nitrogen containing heterocyclics used in the electrolyte to enhance performance also act as corrosion inhibitors with significant stabilization for metals such as iron. These new techniques will be important tools to help develop corrosion resistant metal surfaces and corrosion inhibiting electrolytes for use in industrial scale devices.